2004
DOI: 10.1021/la0360916
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic in Situ Characterization of Organic Monolayer Formation via a Novel Substrate-Mediated Mechanism

Abstract: Ultrahigh vacuum scanning tunneling microscopy data investigating octylsilane (C8H17SiH3) monolayer pattern formation on Au(111) are presented. The irregular monolayer pattern exhibits a 60 A length scale. Formation of the octylsilane monolayer relaxes the Au(111) 23 x square root3 surface reconstruction and ejects surface Au atoms. Au adatom diffusion epitaxially extends the Au(111) crystal lattice via step edge growth and island formation. The chemisorbed monolayer covers the entire Au surface at saturation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
21
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 75 publications
5
21
0
Order By: Relevance
“…2 presents a nearly homogeneous layer with holes embraced by the interconnected terraces. The analogous results were observed by Banaszak Holl and co-workers [28] and in our previous work [27]. Banaszak Holl and co-workers [28] studied the n-octylsilane monolayer pattern formed on Au(111) and found that n-octylsilane monolayer appears an interwoven pattern of elevated sinuous ridges that frequently combine to form loop or knotted feature.…”
Section: The Monolayer Of 18-3-18supporting
confidence: 83%
See 1 more Smart Citation
“…2 presents a nearly homogeneous layer with holes embraced by the interconnected terraces. The analogous results were observed by Banaszak Holl and co-workers [28] and in our previous work [27]. Banaszak Holl and co-workers [28] studied the n-octylsilane monolayer pattern formed on Au(111) and found that n-octylsilane monolayer appears an interwoven pattern of elevated sinuous ridges that frequently combine to form loop or knotted feature.…”
Section: The Monolayer Of 18-3-18supporting
confidence: 83%
“…The analogous results were observed by Banaszak Holl and co-workers [28] and in our previous work [27]. Banaszak Holl and co-workers [28] studied the n-octylsilane monolayer pattern formed on Au(111) and found that n-octylsilane monolayer appears an interwoven pattern of elevated sinuous ridges that frequently combine to form loop or knotted feature. In our previous work, [27] the properties of p-xylyl-bis(dimethyloctadecylammonium bromide) at the air/water interface and its monolayer transferred on mica and quartz slides were investigated, the similar topographical image was acquired at zero surface pressure, which was the network-like labyrinthine interconnected ridges.…”
Section: The Monolayer Of 18-3-18supporting
confidence: 83%
“…With respect to the surface micelles and the two-dimensional structures with nanometer size, several formation mechanisms, such as transient micro-Benard cells [3], dewetting of the water film [42,43], and two-dimensional spinodal decomposition [44][45][46][47][48][49][50], have been proposed.…”
Section: Morphologies Of Langmuir-blodgett Monolayersmentioning
confidence: 99%
“…The spinodal decomposition mechanism can also be applied to one-component systems when temperature is suddenly lowered from above the critical temperature to the spinodal decomposition region where phases are unstable. To our knowledge, at present the monolayers with labyrinthine interconnected structures in experiments are interpreted by means of the spinodal decomposition mechanism only in two works [3,44].…”
Section: Morphologies Of Langmuir-blodgett Monolayersmentioning
confidence: 99%
“…However, the lack of STM image contrast information does not necessarily rule out additional molecular adsorption. Evidence for adsorption is instead found in area-averaged tunnel junction scanning tunneling spectroscopy (STS) data which confirm 75% surface coverage at 5 L octylsilane exposure [17].…”
mentioning
confidence: 97%